Violence and Complicity in J. M. Coetzee's Works - Cichoń, Anna Izabela (Department of Dutch and South African Studies, Faculty of English, 2010)
The aim of the paper is to examine J.M. Coetzee’s treatment of violence in his fiction and to trace the strategies he applies in his books. The perspective of over three decades of his writing that we now have makes it possible to discern an evolution of his representations of atrocities and his rendition of and response to the problems he has formulated in his critical essays on violence published in Doubling the Point. A recognizable feature of Coetzee’s fiction is the theme of complicity of those who are not directly involved in the actual crimes committed by others but who, on various levels, have their share in the oppression and who must cope with their sense of guilt and shame. The works discussed in the paper – Dusklands, Waiting for the Barbarians, Age of Iron and Elizabeth Costello – do not exhaust the complexity of Coetzee’s explorations of aggressiveness but they seem to illustrate important transitions in his oeuvre. The transformations include both modulations of thematic concerns related to violence and modifications of textual devices applied by Coetzee.
Keywords: J. M. Coetzee; violence; complicity